Measuring Process Capability - Rañeses, Nestor O. (Philippine Engineering Journal; Vol 15 No 1 (1994), 2021)
Process capability indices are succinct unitless metric which measures the amount of common cause variation present in a process. They indicate the ability of the process to meet engineering specifications or whether process centering poses a problem. First and second generation indices: C p , C pL , C pu , C pk , k, C pm  and Pearson process capability indices are presented, examined and compared. Single and confidence interval estimates of these indices are described. Finally, applications, drawbacks and uses of these indices are discussed.  Keywords: Process Capability Index, C p , C pL , C pu , C pk , k, C pm , Pearson Capability Index